Free radical scavenging potency of ellagic acid and its derivatives in multiple H+/e‒ processes. (December 2020) - Zheng, Yan-Zhen; Fu, Zhong-Min; Deng, Geng; Guo, Rui; Chen, Da-Fu
Abstract: The reaction energetics of the multiple free radical scavenging mechanisms of ellagic acid and its derivatives were studied by DFT method. Ellagic acid and its derivatives that bear catechol or guaiacyl moieties can proceed multiple free radical scavenging processes. Intramolecular hydrogen-bonds were found in the most stable geometries of the investigated compounds and can influence the antioxidant activity of the related groups and hydrogen atom/proton loss sequence. The stronger hydrogen-bond, the weaker antioxidant activity of the hydrogen atom/proton-donating group. The preferred mechanisms vary among different phases. All of the investigated compounds prefer to trap free radicals by multiple HAT mechanisms in gas and benzene phases. The second HAT reaction preferably occurs in the same catechol or guaiacyl unit of the first HAT group with the formation of stable quinone or benzodioxole. The catechol and guaiacyl moieties not only retain high free radical scavenging ability of the parent compounds but even show increased potency for the second and fourth H + /e ‒ reactions. In water phase, ellagic acid and its derivatives would proceed consecutively PL reactions from the OH groups. The formed di/tri/tetra-anion would proceed one/four electron transfers following with single/double SPLET mechanism and electron donation reactions until forming the stable quinone or benzodioxole. Graphical abstract: The preferred free radical scavenging mechanism of ellagic acid and its derivatives in different phases. Image 1 Highlights: Antioxidative mechanisms for ellagic acid and its derivatives were analysed. Intramolecular hydrogen-bonds can influence the hydrogen atom/proton loss sequence. Ellagic acid and its derivatives proceed through multiple H + /e ‒ processes. The preferred mechanisms vary among the different phases.